Image and Territorial Branding: a modern trend and/or a topical discourse of the present-day life and culture - Zheleznyak, Olga (project baikal, 2018)
Image and branding are modern trends and a topical discourse, a simulation space, a virtual world and the facts of life of civilization, an eternal reflection of authenticity and universality of the promoted product. They influence the achievement of positive reputation of states, regions/territories, cities, corporations/firms, entities, goods and their investment attractiveness. Working with a real space, milieu and culture of the territory allows for revealing the most typical features of the image of the territory and demonstrates both individual, personalized interpretations of the image and the most popular (often already branding) images of the ‘place’.